Regression Analysis of Human Resource Factors on Construction Project Performance in Malang City - Rini Pebri Utari; Wahyu Izza Ramadhan (Universitas Islam Raden Rahmat, Malang, 2026)
The construction sector in Indonesia continues to grow rapidly, including in Malang City, where infrastructure and building projects are expanding significantly. Despite this growth, project success remains highly dependent on human resource performance. Previous studies have examined individual human resource factors; however, limited research has compared the dominant influence of multiple factors within a single model in regional contexts. This study aims to analyze the influence of competence, motivation, loyalty, and work discipline on construction worker performance in Malang City and to identify the most dominant factor. A quantitative approach was employed using primary data from 88 construction workers collected through structured questionnaires and analyzed using multiple linear regression. The results show that all variables have a significant and positive effect on worker performance, with a coefficient of determination (R²) of 0.653, indicating that 65.3% of performance variation is explained by the model. Competence is the most dominant factor (β = 0.907), followed by work discipline (β = 0.653), motivation (β = 0.558), and loyalty (β = 0.511). These findings highlight the importance of technical skills in improving productivity and supporting sustainable construction practices. This study provides empirical evidence and practical insights for improving workforce management and project performance.